Ethical Analysis of Alcohol Advertising in Public Spaces in Denpasar City - I Ketut Sutarwiyasa; I Ketut Setiawan; Evelyn Angelita Pinondang Manurung (Communicatus: Jurnal Ilmu komunikasi, 2025)
As the cultural and tourism center of Bali, Denpasar faces tensions between the economic interests of the tourism industry and the moral obligation to uphold socio-religious values rooted in Balinese Hindu culture. Previous studies have tended to emphasize regulatory aspects or the impacts of alcohol advertising from utilitarian and public health perspectives, while research that explicitly situates Kantian ethics within the context of culturally grounded public spaces remains limited. This study aimed to analyze the practice of alcohol advertising in public spaces in Denpasar City from the perspective of Immanuel Kant’s deontological ethics and to examine its implications for Balinese local cultural values as well as the existing advertising regulatory framework. The research employed a qualitative method, with in-depth interviews, field observations, and policy document analyses as data collection techniques. The informants were policymakers, representatives of the advertising industry, cultural experts, academics, legal practitioners, graphic designers, traditional community leaders, and tourism business actors. The findings indicated that the majority of stakeholders perceive alcohol advertising in public spaces as unethical because it conflicts with prevailing moral values, cultural norms, and regulatory provisions, although younger generations demonstrate limited tolerance under certain conditions. Theoretically, this study contributes by extending the application of Kantian deontological ethics within communication studies and culturally grounded advertising ethics. From a policy perspective, it recommends strengthening advertising regulations and ethical codes that are responsive to Balinese cultural values